2008
DOI: 10.1007/s00442-008-1065-3
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent effects on hatching success of the olive ridley turtle, Lepidochelys olivacea

Abstract: Historically, the olive ridley arribada at Playa Nancite, Costa Rica, was one of the largest olive ridley arribadas in the eastern Pacific with 70,000 nesting females in a year. Recently the Nancite arribada drastically declined. We hypothesized that the population decline at Playa Nancite could have been due to low hatching success as a result of the high density of nests on the beach, such that recruitment to the population was insufficient to balance losses. To test this hypothesis, we examined density-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
9
59
1
1
Order By: Relevance
“…With the absence of major predators on the islands, the main factors regulating hatchling output would be intraspecific destruction of eggs, as suggested by other researchers (Bustard & Tognetti 1969, Girondot et al 2002, Tiwari et al 2006, Mazaris et al 2009), increased microbial activity resulting from a higher nutrient load after a certain nest density threshold is reached (Cornelius et al 1991, Tiwari et al 2006, as well as changes in the incubation environment. Honarvar et al (2008) demonstrated experimentally that increasing the density of olive ridley Lepidochelys olivacea nests resulted in lower hatching success possibly due to higher temperatures, higher carbon dioxide levels, and lower oxygen levels. Tiwari et al (2006) found that below-beach-surface predation, erosion, and beach flooding affected green turtle hatchling production at Tortuguero, Costa Rica, in a density-independent manner.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With the absence of major predators on the islands, the main factors regulating hatchling output would be intraspecific destruction of eggs, as suggested by other researchers (Bustard & Tognetti 1969, Girondot et al 2002, Tiwari et al 2006, Mazaris et al 2009), increased microbial activity resulting from a higher nutrient load after a certain nest density threshold is reached (Cornelius et al 1991, Tiwari et al 2006, as well as changes in the incubation environment. Honarvar et al (2008) demonstrated experimentally that increasing the density of olive ridley Lepidochelys olivacea nests resulted in lower hatching success possibly due to higher temperatures, higher carbon dioxide levels, and lower oxygen levels. Tiwari et al (2006) found that below-beach-surface predation, erosion, and beach flooding affected green turtle hatchling production at Tortuguero, Costa Rica, in a density-independent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Increased nesting densities on East Island would result in density-dependent changes in the nesting environment (Honarvar et al 2008) and in densitydependent factors such as nest destruction by nesting females and disease regulating population size. Females have been observed to destroy incubating nests during their nesting process on East Island (Balazs 1980).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…One experimental approach to testing the effect of intraspecific competition on population growth comprises removing (or adding) individuals and monitoring subsequent population variations (Murdoch 1970, 1994, Massot et al 1992, Adams and Tschinkel 2001, Honarvar et al 2008. A population regulated by intraspecific competition is predicted to be resilient to this kind of manipulation and to return rapidly to its initial state.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of this mortality source is highly dependent on nest density. As the density of nesting females increases, the probability of one female excavating another nest increases (Bustard & Tognetti 1969, Tiwari et al 2006, Honarvar et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Nesting begins in early December on Bahía Barahona and Quinta Playa, and about a month later on Las Bachas and Las Salinas. Early nests are more vulnerable to subsequent destruction from other nesting turtles.Nest destruction by later nesting sea turtles has been observed in high nest density populations such as in green turtles from Tortuguero, Costa Rica (Tiwari et al 2006), and the southern Great Barrier Reef, Australia (Bustard & Tognetti 1969, Limpus et al 2003, in leatherbacks from French Guiana (Giron dot et al 2002), and olive ridleys in Costa Rica (Honarvar et al 2008). Nest destruction rate from nesting females in Tortuguero, Costa Rica, is 4 times higher (Ti wari et al 2006) than our estimates from Bahía Barahona and Quinta Playa, which probably reflects differences in population density.…”
mentioning
confidence: 99%